Análisis de la figura jurídica de las asignaciones forzosas como mecanismo legal de protección de legitimarios y cónyuge sobreviviente. - Arellano Arellano Carmen Piedad (2025)
The present research focuses on a detailed study of the legal concept of forced heirship in Ecuadorian inheritance law, with particular attention to its role as a protective mechanism for legitimaries, primarily children and ascendants, as well as the surviving spouse. This legal institution of inheritance law practically guarantees that certain heirs, known as forced heirs, receive a portion of the deceased's estate, preventing the decedent from depriving them of their right to inherit. This situation is legally established and prevails over the decedent's will. In matters of inheritance law, it is essential to emphasize the patrimonial protection mechanisms established in the current civil regulations, specifically the Civil Code, for the immediate family of the decedent, such as children, parents, and spouse. Forced heirship, as its legal denomination suggests, is established by law. Therefore, determining what constitutes forced heirship, how it should be applied, and to what it refers is significant, especially since, in most cases, family members are unaware of the rules governing inheritance law and the rights that protect them. This research was developed through an analysis of the relevant content of Book III of the Civil Code, titled "Succession by Cause of Death and Gifts Between the Living." This book encompasses the pertinent legal provisions that determine the forms of succession, the ways to access inheritance or legacy, and, above all, the legal mechanisms that ensure the transmission of an individual's estate to their family after their death. It also addresses scenarios where there are no close family members. In this context, forced heirship legally determines how the succession order is implemented and applied at the very moment the succession occurs. Doctrinal analysis is fundamental for building upon previous studies on the legal institution analyzed in this work. Scholars focusing on inheritance law have examined its evolution over time, its underlying principles, and its practical application. Additionally, it is crucial to highlight the importance of forced heirship as a mechanism to protect the rights of heirs, even above the decedent's will, as this is a consistent provision in the Civil Code. The research will also address current issues concerning the legal concept of forced heirship, such as the restrictive or expansive interpretation of legitimaries' rights, tensions with testamentary freedom, and practical challenges that may arise during its application. To develop this research, a qualitative approach was adopted, focusing on doctrinal review and analysis of the legal norms. This qualitative study allows for a detailed examination of the legal and doctrinal regulation, as well as the legal principles underlying this inheritance law figure. Keywords: Forced Heirship, Legitimaries, Legitimacy, Inheritance Law, Forced Heirs, Patrimonial Protection.